Policy support for sustainable crop intensification in Eastern Africa - Yami, M.; Asten, Piet J.A. van (Elsevier, 2017)
Sustainable Crop Intensification (SCI) has been recognized as a means to increase crop productivity and improve rural livelihoods by governments and development partners in Sub Saharan Africa. Designing and implementing policies that address the bottlenecks to SCI interventions is pertinent to address low crop productivity. However, little attention is geared towards analyzing the existing policies and examining their provision in addressing the key challenges to SCI. Based on analysis of policy documents and perception of key policy actors in Ethiopia, Kenya, and Uganda, this paper looks at the level of policy support for SCI in Eastern Africa. Results indicate that lack of incentives to invest in SCI, and poor capacity of agricultural extension system in technology development and dissemination constrain implementation of policies supporting SCI. Mistrust among policy actors over ‘hidden’ interest of international donors in Genetically Modified Organisms (GMOs) and failure to have open discussion to clarify the involvement of multinational companies in regional trade hamper the implementation of policies supporting SCI. Policies lack emphasis on protecting farmers rights' over land tenure and local varieties, posing a challenge to policy harmonization and regional trade. Therefore, developing incentive mechanisms for SCI, and strengthening the capacity of agricultural extension system to meet the requirements of SCI are required. Encouraging public dialogue over the national and regional interests over involvement of multinational companies in regional trade and on GMOs could enhance the acceptability of the policies supporting SCI by many of the agricultural actors. Strengthening farmer groups at different levels could also play important role in protecting farmers' rights in regional trade.